Investigating Weakly Connected 2-Domination in the Complementary Prism of Graphs and in Some Unary Graph Operations - Militante, Mae P.; Tejada, Doli-Jane U.; Seddic, Nadjua E.; Demata, Francis Nixon D.; Campos, Emmanuel (Communications in Mathematics and Applications, 2025)
This paper dealt with the concepts of weakly connected 2-domination in the complementary prisms of graphs and graphs obtained by reducing their edges and vertices. In particular, bounds and exact values of the weakly connected 2-domination number in the complementary prism of graphs, graphs resulting from deleting an edge and vertex and line graphs are presented. In addition, properties of the graphs with weakly connected 2-domination number of complementary prism equal to 2 and 3, are provided.